MENTAL ALERTNESS AMONG PRE-SERVICE TEACHER TRAINESS FROM NAGAON DISTRICT OF ASSAM (International Journal of Food and Nutritional Sciences, 2022)
The statement of the present study is, “Level of Mental Alertness among Pre-Service Teacher Trainees from Nagaon District of Assam.” Based on the problem of the study the objective framed are: (i) to study the mental alertness among the pre-service teacher trainees from Nagaon District of Assam. (ii) to study the relationship between mental alertness among the male and female pre-service teacher trainees from Nagaon District of Assam.